THE INFLUENCE OF PSYCHOLOGICAL CAPITAL IN SHAPING ENTREPRENEURIAL MINDSETS AND ENCOURAGING INNOVATION ORIENTATION AND BUSINESS RESILIENCE IN MSMES - Frederick Rudy Sentosa Rajagukguk; Indra Welly Arifin; Hastuti Handayani Harahap (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the influence of Psychological Capital on Entrepreneurial Mindset and its impact on Innovation Orientation and Business Resilience in Micro, Small, and Medium Enterprises (MSMEs). This study uses a quantitative approach with the Partial Least Squares-based Structural Equation Modeling (SEM-PLS) method using SmartPLS software. The results show that Psychological Capital has a positive and significant influence on Entrepreneurial Mindset as well as Innovation Orientation and Business Resilience. However, Entrepreneurial Mindset does not have a significant direct effect on Innovation Orientation and Business Resilience. Nevertheless, Entrepreneurial Mindset is proven to have a role as a mediating variable in the relationship between Psychological Capital and Innovation Orientation and Business Resilience. This finding confirms that increasing innovation and business resilience in MSMEs is not only directly influenced by psychological capital, but also through the formation of a strong entrepreneurial mindset. Therefore, strengthening the psychological aspects of MSMEs is an important factor in increasing business competitiveness and sustainability.